UNDERSTANDING THE BENEFITS OF FASTING AND THE PREVENTION OF DEGENERATIVE DISEASES WITH THE MAIN SOURCES OF MUHAMMADIYAH TARJIH AND HEALTH EXPERT OPINIONS - Dina Rahma Fadlilah; Triana Srisantyorini; Nurmalia Lusida; Ma’mun Murod Al-Barbasy; Iswan Iswan; Risky Akaputra (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2021)
Worship is doing something that is against the desire of his lust, to magnify His God. According to the scholars of fiqh, worship is doing something to achieve Allah's pleasure and to expect His reward in the hereafter. Fasting comes from Arabic, from which the mufrad shaama-yashuumu-shiyaaman means